102 DISMISSAL OF PATIENTS FROM CHRONIC OPIOID THERAPY: REASONS FOR DISMISSAL AND POTENTIAL INTERVENTIONS. Issue 1 (1st January 2007) - Haq, S.; Yarbrough, W.
Abstract : Introduction: Physicians are in a unique position of being able not only to prescribe pain medications appropriately to patients but also to identify prescription drug abuse when it exists. Aim: To evaluate the reasons for dismissal of patients from chronic opioid therapy and look at possible prevention. Methods: The medical records of patients with chronic pain dismissed from the pain clinic in an outpatient medicine clinic were retrospectively reviewed for the assessment of the reasons leading to the discontinuation of their care. Inclusion criteria included patients with chronic pain ages 18 to 100 seen in the clinic within the last 4 years. The reasons for aberrant behavior were categorized as follows: (1) multiple providers, (2) multiple violations, (3) abusive behavior to clinic staff or physicians, (4) fraud, and (5) illegal drug use. Results: A total of 76 patients' charts were reviewed. Of 76 records, 26 patients (19.7%) had obtained opoids from multiple providers. Twenty-five patients (19%) had multiple requests for early refills, lost prescriptions, etc. Twelve patients (9%) had abusive behavior to the clinic staff and physicians. Eight patients (6%) had committed fraud, such as altering prescriptions, and five patients (3.8%) had their periodic drug screens positive for the illegal drug use. Conclusion: The data revealed that seeking and obtaining controlled substances from different providers and frequent minor violations, such as early refill requests, were the most common reasons for dismissal from the pain clinic. Overt illegal acts, such as forgeries, were the least common. There was no clear-cut evidence in any of these cases of selling or diverting drugs to other people, although there were a couple in which there was some suspicion. It would appear that the vast majority of violations were abuse or addiction related to the individual being treated.